Antibiotic susceptibility and efflux pump activity in uncommon bacterial species associated with conjunctivitis - Obaid, Hussein Ahmed Juma; Madfoon Shaltagh, Suhad Mohammed (Pharmakeftiki, 2025)
This study investigates the antibiotic susceptibility and phenotypic characteristics of uncommon bacterial species associated with conjunctivitis. A total of 150 conjunctival swab samples were collected from patients presenting with symptoms of conjunctivitis at the Al-Nasiriyah Teaching Hospital and the Al-Haboubi General Hospital (Ophthalmology Consultant Unit; Dhi Qar Governorate, Iraq) between August and December 2024. Bacterial isolates were identified based on cultural and microscopic characteristics, supplemented by the Vitek® 2 Compact System (bioMérieux, France). Gram-positive bacteria predominated, with Staphylococcus aureus accounting for 40% of isolates. Several uncommon species were also identified, including Kocuria kristinae, Staphylococcus hominis subsp. hominis, Escherichia coli, Brucella melitensis, Gemella bergeri, Staphylococcus pseudintermedius, and Leuconostoc citreum. Antibiotic resistance profiles were determined using the Kirby–Bauer disk diffusion method, revealing notable resistance to commonly prescribed agents such as erythromycin and ciprofloxacin. Efflux pump activity (a key mechanism contributing to multidrug resistance) was detected in 37.5% of isolates using the ethidium bromide cartwheel method. These findings highlight the importance of robust antibiotic stewardship and underscore the need for continuous surveillance of bacterial resistance patterns in order to optimize therapeutic strategies for conjunctivitis.